Novelty Perspectives on Art and Heraldic Display of Nineteenth Century Historicist Retables in the Temes Banat - Vlăsceanu, Mihaela (Eikón / Imago, 2025)
In this study I will question the function of images and symbols present on a selection of nineteenth-century altars in the Banat region, analyzing the use of heraldic symbols and particular iconography related to the holy kings of Hungary, providing an interpretation of the political engagement of their formulation and use. In order to augment knowledge on their semantic multivalence we will include a topical discussion on the ideas generating their specific morphology and integrated historicism, applying an interdisciplinary methodology, revealing multiple layers of novel meaning and connections.